Fetal Cardiology A Practical Approach to Diagnosis and Management (Springer International Publishing, 2018)
This practical book describes a systematic approach to the ultrasound examination of the fetal heart based on accepted screening recommendations. The written content is enhanced by images and videos of both normal and abnormal sonographic findings. Fetal Cardiology: A Practical Approach to Diagnosis and Management goes further than simply describing core screening views. It includes extended views of the fetal heart, the use of Doppler techniques and assessment of fetal cardiac function. "Variants" which can be encountered in practice are described as well as the features of the major groups of cardiac abnormalities and fetal arrhythmias. Because the authors include experienced fetal and paediatric cardiologists, the focus is not only on diagnostic features but also the approach to postnatal care and prognosis. This content is enhanced by inclusion of chapters relating to associated fetal abnormalities, the genetics of congenital heart disease and new imaging modalities such as MRI of the fetal heart. The book equips all those using ultrasound to image the fetus with a clear concise reference to meet the challenge of new guidelines and to expand their knowledge of complementary echocardiographic techniques and management. It details why prenatal recognition of congenital heart disease is being prioritised to allow for parental choice, recognition of associated abnormalities and improvement of postnatal outcome. As such, this book will be important for all professionals, whether they be a cardiologist, fetal medicine specialist, sonographer or midwife.